Attention Investigation on Children with Attention Deficit Hyperactivity Disorder in Different Genders at School Age - Jingzhi HUANG; Minghe LIN (康复学报)
Objective:To explore the different dimensions of attention in children with attention deficit hyperactivity disorder (ADHD) and normal children of different genders at school age.Methods:A total of 62 children at school age who complied with DSM-V ADHD diagnostic criteria were divided into 32 male ADHD group and 30 female ADHD group, in the meantime, 65 normal children were recruited and divided into 33 male control group and 32 female control group. Chinese Children's Attention Scale was used to evaluate the overall attention and different dimensions of attention in the four groups of children and data was collected for statistical analysis.Results:The performance of children in ADHD group was lower than that of control group in terms of overall attention and four dimensions of attention, including focused attention, sustained attention, selected attention and divided attention (P< 0.05). The performance of male ADHD group was lower than that of male control group and female control group in terms of overall attention and five dimensions of attention, including focused attention, sustained attention, selected attention, divided attention and alternated attention (P< 0.05). The performance of female ADHD group was lower than that of male control group and female control group in terms of overall attention and three dimensions of attention, including focused attention, sustained attention and divided attention (P< 0.05). The performance of male ADHD group was lower than that of female ADHD group in terms of three dimensions of attention, including selected attention, alternated attention and divided attention (P< 0.05). The performance of female ADHD group was lower than that of male ADHD group in terms of sustained attention (P< 0.05).Conclusion:There was no difference in overall attention and different dimensions of attention among normal school-age children of different genders. School-age children with ADHD showed lower performance in overall performance and four dimensions of attention, including focused attention, sustained attention, selected attention and divided attention than normal children. There were quantitative and qualitative differences in different dimensions of attention deficit among children with ADHD of different genders. School-age male children with ADHD had five dimensions of attention deficit while school-age female children with ADHD had three dimensions of attention deficit. Divided attention deficit was more severe in school-age male children with ADHD than in school-age female children with ADHD, while sustained attention was more severe in school-age female children with ADHD than in school-age male children with ADHD.